Proceso de atención de enfermería en paciente adulta mayor de sexo femenino con cáncer de mama. - Román Paladines, Jessica Maricela (2021)
The nursing care process is a tool that helps us to identify the altered needs in the patient based on theoretical and practical knowledge, in order to help in their recovery. The present clinical case was applied to an older adult patient diagnosed with stage III b breast cancer as the main diagnosis. Trying to approach from an epidemiological and pathophysiological point of view to later elaborate, implement and evaluate an individualized nursing care plan. Breast cancer is one of the leading causes of death in women, ranking 11th on the list of general causes of female death. Being an abnormal and disorderly proliferation of malignant mammary cells that produces the uncontrolled growth of a tumor within the breast, which has the ability to invade other organs. For the nursing staff, it is very important to implement the intervention measures that best suit the patient, with the help of the NANDA, NIC and NOC taxonomies, to provide a timely nursing diagnosis to create a care plan prioritizing their symptoms. The satisfactorily obtained results showed timely progress, thus creating an environment that facilitates trust between nurse and patient, to continue with the pathology process.